Wi-Fi Direct based WSN Node Deployment in Underground Mine Tunnels - MALGAZHDAR, Daniyar; IKEDA, Hajime; TORIYA, Hisatoshi; SHIONOIRI, Takaya; SUORINENI, Fidelis; ADACHI, Tsuyoshi; KAWAMURA, Youhei (The Society of Materials Engineering for Resources of Japan, 2022)
Fast data transmission is becoming a key parameter in mine planning, operation, and safety. Therefore WSNs (wireless sensor networks) is taking a leading role in underground mine environment communication. WSNs can measure mine environmental parameters by sensors to provide quick and detailed communication for comprehensive assessment of the situation, during both regular operations and emergency situations. Nowadays, WSNs are developing very fast, getting more compact, energy and cost-effi cient. On the other hand, underground mines have very specifi c working conditions characterized by narrow spaces, dynamic environments, and high humidity. This demands WSN nodes to be specifi cally arranged to be functioning effi ciently considering limited throughput and energy resources. Wi-Fi Direct is a wireless connection type used in WSN and supported by many manufacturers around the world. This research will consider using WiFi Direct and ad hoc networks for WSN and will analyze the deployment of WSN nodes in underground mine environments. The physical experiment measuring the performance of deterministic Wi-Fi Direct mode node deployment in Osarizawa experimental underground mine was conducted. The experiment indicated that the data packets can be sent without loss to a distance up to a 140 m in a straight tunnel with 4 m2 crosssection area. The obtained results were applied to planned WSN node deployment at Tishinskiy mine site in East Kazakhstan
Keywords: WSN; Wi-Fi Direct; Node deployment